2018
DOI: 10.1128/jvi.01368-18
|View full text |Cite
|
Sign up to set email alerts
|

HOIL1 Is Essential for the Induction of Type I and III Interferons by MDA5 and Regulates Persistent Murine Norovirus Infection

Abstract: The linear ubiquitin chain assembly complex (LUBAC), composed of heme-oxidized IRP2 ubiquitin ligase 1 (HOIL1), HOIL1-interacting protein (HOIP), and SHANK-associated RH domain-interacting protein (SHARPIN), is a crucial regulator of multiple immune signaling pathways. In humans, HOIL1 or HOIP deficiency is associated with an immune disorder involving autoinflammation, immunodeficiency, and inflammatory bowel disease (IBD)-like symptoms. During viral infection, LUBAC is reported to inhibit the induction of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 90 publications
1
47
0
Order By: Relevance
“…Various PAMPs activate the Toll-like receptors (TLRs)mediated NF-κB and IFN antiviral pathways 1 . Although LUBAC activity reportedly down-regulate the type I IFN production pathway 32,33 , recent studies suggested that the LUBAC is necessary for the TLR-mediated interferon regulatory factor 3 (IRF3) activation [34][35][36] . Among the PAMPs, HOIPIN-1 suppressed the NF-κB activation induced by CpG, a ligand for TLR9 (ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various PAMPs activate the Toll-like receptors (TLRs)mediated NF-κB and IFN antiviral pathways 1 . Although LUBAC activity reportedly down-regulate the type I IFN production pathway 32,33 , recent studies suggested that the LUBAC is necessary for the TLR-mediated interferon regulatory factor 3 (IRF3) activation [34][35][36] . Among the PAMPs, HOIPIN-1 suppressed the NF-κB activation induced by CpG, a ligand for TLR9 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effects of LUBAC on the IFN antiviral pathway have been controversial, several recent reports suggested that the LUBAC activity is crucial for the IRF3 activation [34][35][36] . Moreover, OTULIN, a linear ubiquitin-specific deubiquitinase, was revealed to down-regulate the IFN induction pathway 52 , suggesting that linear ubiquitination seems to regulate antiviral pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which HuNoV is sensed by the infected cells is not currently known; however, data from MNV suggest a clear role for Mda5-mediated sensing in the restriction of norovirus replication both in cell culture and in vivo (61). The sensing of MNV RNA occurs in a process that requires the HOIL1 component of the linear ubiquitin chain assembly complex (LUBAC) complex (62). Other components of the RNA sensing pathways, including mitochondrial antiviral-signaling protein (MAVS), IRF3, and IRF7, have been implicated in the innate response to MNV (61,62), but the role that they play in sensing of HuNoV RNA is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The sensing of MNV RNA occurs in a process that requires the HOIL1 component of the linear ubiquitin chain assembly complex (LUBAC) complex (62). Other components of the RNA sensing pathways, including mitochondrial antiviral-signaling protein (MAVS), IRF3, and IRF7, have been implicated in the innate response to MNV (61,62), but the role that they play in sensing of HuNoV RNA is unknown. In addition to targeting STAT1 for degradation (63), the PIV5 V protein is known to also inhibit the activity of Mda5 (35).…”
Section: Discussionmentioning
confidence: 99%
“…RAD51AP1 facilitates homologous recombination of host DNA [107], while SEC61G functions in membrane protein translocation and incorporation into the endoplasmic reticulum [108]. The interactions between HuNoV and these genes are speculative; however IRF3 [109,110], IRF7 [110,111], MDA5 [112][113][114][115], RIG-I [35,111,113,114], TLR3 [112], and TLR7 [114,116,117] have been previously implicated in NoV responses. Of note, TLR2 enhances cytokine production upon the detection of rotavirus [118].…”
Section: Discussionmentioning
confidence: 99%